ERGONOMIC ENVIRONMENT PREVENTING ACCIDENTS FROM NATURAL DISASTERS - Gempur Santoso, (International Journal of Social Science, 2022)
Life and human life are in the natural environment. In nature can not be separated from natural disasters. Risks so as not to be overwritten by natural disasters require preventive measures. This paper discusses about the ergonomic environment as a measure to prevent accidents due to living and doing activities in nature on sloped land. This scientific writing design uses descriptive by presenting several opinions or research results. Methods of data collection using literature study. The inference method is done using deductive. Conclusion: a). The slope of the slope has a very significant effect on soil damage, including causing landslides, so that a slope of 0 -7 degrees is flat and very sloping land, the best for settlements and a slope of 7 - 15 degrees is sloping land, not dangerous for humans to build settlements, only requires soil hardening/accompaniment treatment. b). Ergonomic natural environment is a deep ecosystem shaping the terrestrial and aquatic environments to create within human and natural boundaries so that the natural work environment makes human activities safe, secure, comfortable, and healthy in life. Suggestion: It is hoped that the community will pay attention to ergonomic conditions, harden or provide hard assistance on sloped land, and avoid living on steep and steep slopes, so as to avoid the risk of landslides